Bibliometric Analysis and Visualization: Fraud Accounting Research - Winarto, Wahid Wachyu Adi (Asia Pacific Fraud Journal, 2025)
This study systematically examines the intellectual structure of accounting fraud research, identifying key trends, gaps, and opportunities to guide future scholarly and practical efforts in fraud detection and prevention. Using bibliometric analysis, we evaluate 193 Scopus-indexed articles (1993–2024) with R-Studio, VOSviewer, and Excel to map influential authors, keyword networks, citation trends, and collaboration patterns. The field gained momentum post-2016, with the United State dominating research output. However, studies remain siloed most focus on fraud detection rather than prevention, and minimal cross-author collaboration exists. Keyword analysis reveals evolving themes, yet few explore accounting techniques as proactive fraud deterrents. The study relies on Scopus data, potentially excluding relevant non-indexed works. Additionally, bibliometric analysis emphasizes trends over in-depth theoretical critique. Practitioners gain a consolidated view of fraud research, while researchers can leverage identified gaps, particularly in prevention strategies to design impactful studies. Policymakers may use findings to encourage interdisciplinary collaboration. This is among the first bibliometric reviews to systematically assess accounting fraud literature, offering a visual and analytical roadmap for future innovation in fraud prevention. By highlighting understudied areas, it challenges researchers to move beyond detection toward actionable solutions.